UK Cryptoassets Taskforce publishes its final report. Issue 2 (9th May 2019) - Maxson, Sam; Davis, Stuart; Moulton, Rob
Abstract : Purpose: To analyse the final report of the UK Cryptoassets Taskforce published in October 2018 and discuss the UK's policy and regulatory approach to crypto-assets and distributed ledger technology in financial services. Design/methodology/approach: This article considers some of the key aspects of the final report of the UK Cryptoassets Taskforce and provides a summary of the next steps the UK authorities have committed to taking in relation to regulation of crypto-assets in the UK. Findings: The approach to regulation of crypto-assets in the UK is evolving and the relevant UK authorities are continuing to improve their understanding of crypto-assets in order to assess the appropriate type and level of regulation that should apply to them. Whilst risks relating to consumer detriment and anti-money laundering have been identified as needing to be addressed as a matter of priority, the UK authorities appear to be taking a measured approach to regulation of crypto-assets. They also remain supportive of the adoption of distributed ledger technology in financial services, whilst noting some potential challenges to scalability. Originality/value: This article contains valuable information about current policy direction and regulatory thinking in the UK in relation to crypto-assets, and analysis from leading FinTech lawyers.